Electrochemical redox of Cd(II) mediated by activated carbon modified glassy carbon electrode. - Tan, Wee Tee; Radhi, M. M.; Ab. Rahman, Mohamad Zaki; Kassim, Anuar (Oriental Scientific Publishing, 2010)
The use of a glassy carbon electrode (GCE) modified by activated carbon (AC) mediates the redox of (CdCl2) in 0.1 M aqueous solution of potassium chloride (KCl) supporting electrolyte. During cyclic voltammetry, two oxidation and two reduction current peaks of Cd2+ were appearing at +0.4, -0.6, +0.6 and -1.8V respectively, versus Ag/AgCl. The redox current of Cd2+ was enhanced by two folds at AC modified GCE and about five folds in acidic media. The oxidation peak of Cd2+ was shifted to lower potential by approximately 5mV and for the reduction peak was shifted to 0 mV when AC modified GCE in acidic pH. The sensitivity under condition of cyclic voltammetry was significantly dependent on pH, concentration of AA and temperature. Interference with Cd2+ was observed in different metal ions, such as Cu2+ Mn2+ and Hg2+. The current enhancement appeared and causes further increase in the two reduction peaks and one of oxidation peak of Cd2+, in contrast the other oxidation current peak decrease when increase the concentration of the interference metals. The surface charge determined by chronocoulometry (CC) of Cd2+ at AC/GCE in presence of AA solution was more conductive than use of GCE. Diffusion coefficient determined by chronoamperometry (CA) for Cd2+ at AC/GCE in presence of AA was promising results.